Dynamic impacts of U.S. energy development on agricultural land use. (February 2020) - Fitzgerald, Timothy; Kuwayama, Yusuke; Olmstead, Sheila; Thompson, Alexandra
Abstract: The land-use impacts of the rapid expansion of U.S. oil and gas infrastructure since the early 2000s are a focus of local, state, and federal policymakers. Agriculture is the dominant land use in many areas with active energy development. Prior studies find that energy development displaces agriculture and assume that this effect is both permanent and homogeneous. We take a novel approach, analyzing landowners' capacity to both anticipate displaced production prior to the drilling of oil and gas wells, and reclaim some land once wells are in production. Using North Dakota's Bakken Shale as a case study, we merge agricultural land-use data from 2006 to 2014 with locations and drilling dates of oil and gas wells. We then use panel fixed-effects models to estimate the spatially- and intertemporally-heterogeneous effects of additional wells on agricultural land. We find that drilling is associated with reduced surrounding crop cover and increased fallow acreage. Importantly, the duration of these effects differs across agricultural land covers, and effects are in some cases temporary. Our analysis suggests that overlooking dynamic land use impacts may overestimate the cumulative net impact of oil and gas development on agricultural land uses by up to a factor of two. Highlights: Oil and gas development displaces planted crops. Landowner reactions to oil and gas wells mitigate some of that effect over time. Farmers anticipate displacement by increasing planted acreage prior to drilling. Ignoring dynamic response overestimates the net effect by up to a factor of two. Concern about energy sprawl must consider dynamic impacts.